Botulinum neurotoxin type A alleviates mechanical hypersensitivity associated with infraorbital nerve constriction injury in rats. (10th January 2017) - Noma, Noboru; Watanabe, Kosuke; Sato, Yuka; Imamura, Yoshiki; Yamamoto, Yumiko; Ito, Reio; Maruno, Mitsuru; Shimizu, Kohei; Iwata, Koichi
Highlights: BoNT-A alleviated ION-CCI-induced mechanical allodynia and hyperalgesia. High-dose BoNT-A suppressed nocifensive behavior. BoNT-A decreased Vc neuronal responses after noxious stimulation. Abstract: We investigated the effect of botulinum neurotoxin type A (BoNT-A) on mechanical allodynia and hyperalgesia associated with infraorbital nerve constriction (ION-CCI) in rats. ION-CCI rats received a subcutaneous BoNT-A injection into the whisker pad area on day 7 postoperatively and underwent pain assessment on days 14 and 21 postoperatively. Rats were assigned to one of four treatment groups (n = 5 each): ION-CCI + BoNT-A 20 pg (low-dose group), ION-CCI + BoNT-A 200 pg (high-dose group), ION-CCI + saline, and Sham. Mechanical allodynia and hyperalgesia were evaluated preoperatively (baseline) and on days 7, 14, and 21 postoperatively. After noxious mechanical stimulation of whisker pad skin, the number and distribution pattern of the phosphorylated extracellular signal-regulated kinase (pERK)-immunoreactive (IR) neurons were analyzed in the trigeminal spinal subnucleus caudalis (Vc) and upper cervical spinal cord (C1-C2). On day 21, nocifensive behavior was attenuated by high-dose but not low-dose BoNT-A administration. In addition, after noxious mechanical stimulation of whisker pad skin, the numbers of pERK-IR cells in the superficial laminae of Vc and C1-C2 were significantly lower in the high-dose BoNT-A group than in the ION-CCI + saline group. The present findings suggest that, by suppressing Vc neuronal activity, high-dose intradermal injection of BoNT-A at the site of ION innervation alleviates mechanical facial allodynia and hyperalgesia associated with ION-CCI.